2021
DOI: 10.1007/s13340-021-00515-4
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-glucose cotransporter inhibitors may reduce the risk of pneumonia: an updated meta-analysis of cardiovascular outcome trials

Abstract: The present meta-analysis included 8 cardiovascular outcome trials with 57,185 patients at high cardiometabolic risk. In comparison with placebo, treatment with sodium-glucose cotransporter inhibitors was associated with a significantly lower risk of pneumonia (RR 0.85, 95% CI 0.76–0.95, p = 0.004; I 2 = 0, p = 0.48). Supplementary Information The online version contains supplementary material available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In a meta-analysis of nine randomised controlled trials, SGLT-2 inhibitors were associated with a trend towards a reduced risk of new onset of chronic obstructive pulmonary disease (risk ratio 0.79, 0.61 to 1.02). 51 Furthermore, large observational studies and a meta-analysis of cardiovascular outcome trials have associated SGLT-2 inhibitors with a decreased risk of pneumonia, 10 11 52 a condition that often leads to chronic obstructive pulmonary disease exacerbations. The mechanisms behind heterogeneous findings of SGLT-2 inhibitors preventing severe but not moderate chronic obstructive pulmonary disease exacerbations are unclear and should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of nine randomised controlled trials, SGLT-2 inhibitors were associated with a trend towards a reduced risk of new onset of chronic obstructive pulmonary disease (risk ratio 0.79, 0.61 to 1.02). 51 Furthermore, large observational studies and a meta-analysis of cardiovascular outcome trials have associated SGLT-2 inhibitors with a decreased risk of pneumonia, 10 11 52 a condition that often leads to chronic obstructive pulmonary disease exacerbations. The mechanisms behind heterogeneous findings of SGLT-2 inhibitors preventing severe but not moderate chronic obstructive pulmonary disease exacerbations are unclear and should be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar effects were not reported for other classes of glucose-lowering drugs, including sulfonylurea (10), thiazolidinediones (10), and dipeptidyl peptidase-4 inhibitors (DPP4is) (11), while the association of SGLT2is with pneumonia remains largely unclear. A recent meta-analysis of 8 placebo-controlled clinical trials reported a reduced risk of pneumonia among participants treated with SGLT2is (12). However, clinical trials often include highly selected patients and, hence, compromise the generalizability to the real-world population.…”
Section: Introductionmentioning
confidence: 99%